Soul Food: [Re]framing the African-American Farming Crisis Using the Culture-Centered Approach - Carter, Andrew Laurence; Alexander, Adam (Frontiers in Communication, 2020)
Historically, African-American farmers faced a long and challenging struggle to own land and operate independently. In recent years, several factors, including unfair policy legislation, institutionalized racism, the mechanization of agriculture and increases in agricultural technology have exacerbated land loss and decreases in farm ownership. Currently, African-American farmers are vastly underrepresented, comprising just 2% of the nation’s farmers, 0.5% of farmland and 0.2% of total agricultural sales. As a site for inquiry, this topic has been examined across many academic sub-disciplines, however, the literature not explored how the erasure of the African-American farmer influences the conversation about broader diet-related health disparities in the U.S. This overlooked perspective represents a novel approach to rethinking public health interventions and may improve methods for communicating messages about healthy eating to the African American community. In this essay, we extend Dutta’s (2008) Culture-Centered Approach (CCA) to foreground the lived experiences and perspectives of a small cohort of African-American farmers (n=12) living in the U.S. Mid-South as an entry point to address this underexamined area of research and inform future methodological directions of study. Two key themes emerged from the thematic analysis: (1) erasure of the African-American farming tradition and land loss; and (2) solutions to change. Drawing on the understanding that systematic land loss in the African-American community has contributed to wealth disparities between African-Americans and Whites, we argue that the erasure of the African-American farming tradition within mainstream discourses has created communication inequities that disenfranchise the African-American community and may contribute to broader health inequities in food system. Our findings may offer important insights into the methodological development of more effective health campaigns within these communities.